2018
DOI: 10.1080/09273948.2018.1424342
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Intravitreal Dexamethasone Implant for Refractory Uveitic Macular Edema in Adults and Children

Abstract: Intravitreal DEX implant is safe and effective adjunct therapy. It reduces dependence on systemic steroids, immunosuppressives and provides long-term effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
4
8
0
1
Order By: Relevance
“…The results of this study are similar to prior retrospective studies that demonstrated favorable visual outcomes in pediatric patients with macular edema of various noninfectious etiologies ( [3,6], .and [5].) In the series by Eiger-Moscovich et al of 25 children (33 eyes), 75.8% achieved resolution of macular edema by 24 months.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are similar to prior retrospective studies that demonstrated favorable visual outcomes in pediatric patients with macular edema of various noninfectious etiologies ( [3,6], .and [5].) In the series by Eiger-Moscovich et al of 25 children (33 eyes), 75.8% achieved resolution of macular edema by 24 months.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are similar to prior retrospective studies that demonstrated favorable visual outcomes in pediatric patients with macular edema of various non-infectious etiologies (Eiger-Moscovich et al 2019, Shulman et al 2012., and Ratra et al 2018 In the series by Eiger-Moscovich et al of 25 children (33 eyes), 75.8% achieved resolution of macular edema by 24 months. Patients in their series had similar uveitis etiologies and also received a varied combination of treatment regimens, including a combination of local corticosteroid injections or dexamethasone implants, systemic corticosteroids, antimetabolites and anti-TNF alpha agents.…”
Section: Discussionsupporting
confidence: 88%
“…Ratra et al, investigated the role of Dex in nonresponsive ME secondary to chronic NIUs in adults and children, reporting a significant VA improvement and a good safety profile [57]. Moreover, a single injection of Ozurdex was safe and effective, as an additional treatment to systemic immunomodulatory drugs, in the treatment of refractory Behcet posterior uveitis for a 6-month period [58,59].…”
Section: Evidence Of the Efficacy Of Dex In Posterior Non-infectious mentioning
confidence: 99%